The Effect of Weather Changes on Movement in MV. Palung Mas - Arleiny, Arleiny; Kurnia, Rahmat; Nurmala, Eka; Fauzi, Ahmad; Raihannah, Putro (PT. Alpha Trianguli Australis, 2025)
Weather changes are the effects of climate change that occur due to environmental changes. IMO (International Maritime Organization) has tried hard to minimize accidents by holding conventions. Because ship accidents can occur due to unpredictable weather and lack of expertise of the watch officer or helmsman in controlling the ship's maneuver. This study is a qualitative study that aims to understand the phenomenon in depth through exploration of the meaning, experience, and views of the research subjects in a certain context. The results of this study are: 1) Factors that influence the maneuver of the MV. Palung Mas include ship design, type and placement of engines, steering system, cargo conditions, water and weather conditions, crew expertise and experience, depth and navigation space; 2) Performance of maneuvering on the MV. Palung Mas includes response to the steering system, efficiency of the propulsion system, maneuvering in full load and ballast conditions, the influence of external factors, the ability to stop the ship, crew expertise and technological support; and 3) Ship maneuvering strategy during bad weather on the MV. Palung Mas includes adjusting the ship's speed, choosing the right course, optimizing the propulsion and steering systems, regulating the distribution of cargo and ballast, utilizing weather and navigation information, increasing crew alertness, maintaining communication with external parties, avoiding dangerous areas, being alert in emergencies, using the ship's automation system.